Legal Liability of Heirs for Debtor's Current Account (KRK) Credit Obligations after Death - Muhammad Khairul Imam; Fahrizal S.Siagian (Jurnal Restorasi : Hukum dan Politik, 2026)
A Current Account Credit Facility (KRK) is a flexible form of bank credit that can be used repeatedly according to the debtor's needs within the agreed credit limit. However, legal issues arise when the debtor dies before their debt obligations are settled, raising questions about the extent to which the heirs can be held liable for the debt. This study aims to analyse the legal responsibility of heirs for the debtor's KRK debt obligations after death and the limits of liability that can be imposed on heirs based on inheritance law and contract law provisions. The research method used is legal research with a regulatory and conceptual approach, through analysis of the legal norms governing inheritance, obligations, and banking credit agreements. The results of the study show that, in principle, the debtor's debt obligations are not extinguished by death but are transferred to the estate, which can be claimed by creditors. Heirs are basically only liable to the extent of the value of the inheritance they receive, so that liability is not absolutely attached to the person of the heir. However, in banking practice, there is often an imbalance in legal positions due to credit agreement clauses that extend the burden on heirs, thereby potentially giving rise to disputes. Therefore, it is necessary to affirm the limits of the heirs' liability proportionally in order to ensure legal certainty and protection for the heirs without eliminating the bank's rights as a creditor in collecting the debtor's debt obligations.